2020
DOI: 10.1007/s11705-020-1948-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hierarchical single-crystal ZSM-5 zeolites with different Si/Al ratios on its pore structure and catalytic performance

Abstract: Hierarchical single-crystal ZSM-5 zeolites with different Si/Al ratios (Hier-ZSM-5-x, where x = 50, 100, 150 and 200) were synthesized using an ordered mesoporous carbon-silica composite as hard template. Hier-ZSM-5-x exhibits improved mass transport properties, excellent mechanical and hydrothermal stability, and higher catalytic activity than commercial bulk zeolites in the benzyl alcohol self-etherification reaction. Results show that a decrease in the Si/Al ratio in hierarchical single-crystal ZSM-5 zeolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…In general, para -xylene can reach thermodynamic equilibrium rapidly in the absence of steric constraints. 31 Over Pt/Mon-EU with abundant mesopores, the selectivity of para -xylene attained was much closer to its thermodynamic equilibrium compared with that of Pt/Con-EU.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…In general, para -xylene can reach thermodynamic equilibrium rapidly in the absence of steric constraints. 31 Over Pt/Mon-EU with abundant mesopores, the selectivity of para -xylene attained was much closer to its thermodynamic equilibrium compared with that of Pt/Con-EU.…”
Section: Resultsmentioning
confidence: 88%
“…13,30 Thus, the peak intensity ratio of Q 4 / Q 3 could be applied to represent the degree of condensation degree of silicon species in zeolite materials. 31 According to the results of fitting (Table S1†), the much lower Q 4 / Q 3 ratio of Mon-EU-Pre ( Q 4 / Q 3 = 1.3) suggested a low degree of condensation of the Si–OH bond owing to the presence of abundant amorphous silica (from uncrystallized Z-Powder and extra added SA-Powder) in zeolite precursors. On the contrary, the higher Q 4 / Q 3 ratio of Mon-EU ( Q 4 / Q 3 = 5.7) indicated the transformation of Si–OH to Si–O–Si bonds in a zeolite framework after recrystallization of Mon-EU-Pre in the recycled mother liquor.…”
Section: Resultsmentioning
confidence: 96%
“… When P/P 0 > 0.75, the amount of N 2 adsorption increased abruptly. This indicated that there are some macropores or mesopores in parent Z20 . It should be noted that the adsorption amount of N 2 decreases with the increase of the number of SiO 2 depositions.…”
Section: Introductionmentioning
confidence: 88%
“…This indicated that there are some macropores or mesopores in parent Z20. 37 It should be noted that the adsorption amount of N 2 decreases with the increase of the number of SiO 2 depositions. This phenomenon can be explained by the easier deposition of SiO 2 in macropores and mesopores.…”
Section: Introductionmentioning
confidence: 95%
“…Zeolite is a crystalline aluminosilicate with tetrahedral structures, periodic channels, and cage structures. It is widely used in the heterogeneous catalytic process of the petrochemical industry. Zeolite with MTW topology has attracted much attention due to its distinctive structure. , MTW zeolite, which belongs to the monoclinic C 2/ m , a = 25.552 Å, b = 5.256 Å, c = 12.117 Å, and β = 109.312°, was first synthesized by Rohrbaugh et al The main channel is a one-dimensional (1D) 12-membered ring. , MTW zeolite can be used in many reactions, such as catalytic cracking, , isomerization, and alkylation reactions …”
Section: Introductionmentioning
confidence: 99%